2012
DOI: 10.1016/j.juro.2012.03.048
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes and Long-Term Resolution in Patients with Persistent Vesicoureteral Reflux After Open Ureteral Reimplantation

Abstract: Purpose-Success rates of ureteral reimplantation for primary vesicoureteral reflux (VUR) are high. Few studies document the natural history of children with persistent VUR. We reviewed their clinical outcomes and long-term resolution.Materials and Methods-We performed a retrospective review of all children with persistent VUR (grade≥1) into the reimplanted ureter(s) on initial cystogram after reimplantation for primary VUR at our institution from January 1990 -December 2002. We evaluated subsequent cystograms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 14 publications
3
10
0
Order By: Relevance
“…The patient characteristics revealed that 60% of the patients were female, 66% had bilateral disease, 70% had scarred kidneys and more than 20% had history of previous endoscopic injection. These figures are in accordance with the literature and indications for open surgery (8).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The patient characteristics revealed that 60% of the patients were female, 66% had bilateral disease, 70% had scarred kidneys and more than 20% had history of previous endoscopic injection. These figures are in accordance with the literature and indications for open surgery (8).…”
Section: Discussionsupporting
confidence: 92%
“…However, the surgical success rates didn't differ regarding the surgical technique. Unlike the endoscopic injection techniques (10), success of open UNC does not seem to be affected by the grade of reflux or the presence of voiding dysfunction (8,11,12). Similarly, our results revealed that UNC had a constant success rate regardless of the grade of VUR, presence of voiding dysfunction and also was not affected by the number of the preoperative breakthrough infections, presence of renal scar or the age of the patient.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…While we did not repeat VCUG in any patient with persistent VUR, studies suggest that the natural history is eventual resolution ( 21 ). Hubert et al ( 25 ) reported persistent VUR in 27.8% of their cohort, with spontaneous resolution in all cases that were grade 1. In our series, all 4 cases of persistent VUR were grade 1 ( 24 ).…”
Section: Discussionmentioning
confidence: 88%
“…Currently, the published data are conflicting regarding the complication profile of RALUR [7e10] with multi-institutional pooled data demonstrating high rates of persistent reflux and reoperation [10], whereas a large prospective single-surgeon series reported no complications [11]. This exists in comparison to OUR, which has a robust literature of favorable short and long-term outcomes and low complication rates [12,13]. Similarly, direct costs have increased with use of robot-assisted technology [6].…”
Section: Introductionmentioning
confidence: 99%